ANALYSIS OF CONTACTLESS RADIO FREQUENCY IDENTIFICATION TECHNOLOGIES AND ITS USAGE IN REZEKNE CITY INFRASTRUCTURE OBJECTS - Zalužinskis, Artūrs; Zorins, Aleksejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
Author made the analysis of usage of contactless radio frequency identification technologies in Rezekne city infrastructure objects. Author provides the main types of radio frequency hardware, working principles and worldwide usage statistics. In the conclusion of the paper, author describes the further development opportunities of the radio frequency identification technologies